Avaliação da estrutura populacional e do crescimento de bovinos de grupos genéticos formadores da raça Purunã - Oliveira, Kaliane Nascimento de (2016)
The objective of this study was to estimate the growth pattern and describe the population structure, effective size and the coefficient of inbreeding of cattle crossed from different genetic groups involved in the formation of the race Purunã. We used data from the registry for cattle of Instituto Agronômico do Paraná. We used the model of non-linear regression of Brody with different configurations of models. The first model considered that there is no restriction on the parametric space (M1), and the other models (M2, M3 and M4) had different numbers of restrictions. The comparison of the models gave the following contrasts: C1 = G x F; C2 = G x H; C3 = G x E; C4 = F x H; C5 = F x E and C6 = H x E. For the calculation of population parameters, the database was divided into three generations. We calculated the coefficient of inbreeding population and the effective population size and the integrality of the pedigree. The results showed that the M1, M2 and M3 presented values of A and k overestimated in relation to the M4. The growth curves between the C1, C3, C5 and C6 showed better adaptation to the M1. The M2 was more suitable for the estimation of parameters for the contrast C2. In contrast, C4, the M3 has been shown to be more efficient. It was obtained greater value for the group G (771.9); followed by the F (677.2); H (583.7) and E (452.1). The largest k value was observed in the comparison of group F WITH G (0.000948). There is a difference between the growth pattern of the genetic groups. Individuals with composition 1/4 CarCh + 1/4 CnAb are heavier and late, while those with composition ¼ AbCn + 1/4 ChCar are Early. As the analysis of population structure, the effective size of the population was 2,317.93; and 483.31, 720.55, 1,101.46 for generations 1, 2 and 3, respectively. Of the 11,923 animals in the database, 840 had a coefficient of inbreeding above zero, with a coefficient of inbreeding middle of 3.2%. The study of the integrality of the pedigree showed that the 11,923 animals, it was 2.64% of parents, 18.78% of mothers, 1.80% of the paternal grandparents, 9.32% of maternal grandparents, 1.25% of the paternal great-grandfather and 5.36% of maternal great-grandfather. The population parameters remained within the established. The population precursor of race Purunã has a small number of animals inbred, with levels of inbreeding. It is recommended that the selectors using bulls and arrays of wide.